Development of an interoperable Web Application to work in areas with limited connectivity in the Admissibility Processes of Activities, as a complement to Smart Cities - Vargas Huanaco, Roman (2024)
Smart cities are characterized by comprehensive connectivity, for which a level of integration is needed, for which integration must mature. In this sense, we find connectivity problems that occur in the areas of the Peruvian jungle, with interferences that cause cuts in the different services that use the Internet connection, such as web systems, for which the National Commission for Development and Life without Drugs (DEVIDA) is a public entity, has its headquarters in a district of the Peruvian Amazon jungle. The admissibility of activities is the registration of all activities to be carried out. These activities are characterized by controlling coca leaf plantations, as well as their eradication campaigns, being important to have the information in real time. Carrying out an analysis of similar works, we found works where XML messaging is used to achieve interoperability between the various systems, which is adopted in the present work. A web system has been designed that integrates connectivity detection functionalities in order to send information through an alternate mechanism, based on the exchange of information via XML messaging. The results indicate that it is possible to have information in real time, in all locations, which achieves interoperability between different systems.